Studi Banding PASA FISIP Unsri – Himagara FISIP Unila: Strategi Pertukaran Gagasan dan Pembelajaran Organisasi - Pamungkas, Pandu; Hapsari, Rindy Putri; Wijayanti, Zetia; Masruroh, Ina; Suryani, Riza Adelia; Syafebri, Arrahman (Abdimas Universal, 2026)
The comparative study activity between PASA Unsri - Himagara Unila student associations is a form of community service in the realm of higher education that aims to encourage the exchange of ideas, organizational learning, and improve the quality of student human resources. This article describes the mentoring activities in a comparative study between two student associations from different universities, namely PASA Unsri – Himagara Unila. The mentoring focused on facilitating formal forums such as introductory sessions, presentations of excellent work programs, open discussions, and questions and answers related to organizational practices, academic activities, and human resource development. This research used a descriptive qualitative approach with participatory observation and interview methods. The results showed that this comparative study was able to open new perspectives between associations, strengthen student networks, and foster a spirit of collaboration in organizational management. This activity is recommended as a model for sustainable capacity building of student organizations. In addition, this activity is expected to strengthen synergy between organizations, create a collaborative climate, and provide tangible benefits for all members and the academic community.